2014
DOI: 10.1016/j.stemcr.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Interferon-α-Induced Depression and Neural Stem Cell Dysfunction

Abstract: SummaryNew neurons generated by the neural stem cells (NSCs) in the adult hippocampus play an important role in emotional regulation and respond to the action of antidepressants. Depression is a common and serious side effect of interferon-α (IFN-α), which limits its use as an antiviral and antitumor drug. However, the mechanism(s) underlying IFN-induced depression are largely unknown. Using a comprehensive battery of behavioral tests, we found that mice subjected to IFN-α treatment exhibited a depression-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 75 publications
5
62
1
4
Order By: Relevance
“…IFN-␣ has previously been shown to induce depression-like behaviour in both clinical [2,22,23,] and pre-clinical studies [20,25,36,37], although some studies have not found the same [6,33]. The inconsistency may arise from the IFN-␣ type, as some human IFN-␣ does not have biological activity in rodents, as discussed by [6,17,33].…”
Section: Ifn-˛caused Depression-like Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-␣ has previously been shown to induce depression-like behaviour in both clinical [2,22,23,] and pre-clinical studies [20,25,36,37], although some studies have not found the same [6,33]. The inconsistency may arise from the IFN-␣ type, as some human IFN-␣ does not have biological activity in rodents, as discussed by [6,17,33].…”
Section: Ifn-˛caused Depression-like Behaviourmentioning
confidence: 99%
“…Indeed, we found a positive correlation between immobility and hippocampal quinolinic acid levels. Interestingly, recent findings have revealed that IFN-␣ suppresses hippocampal neural stem cell proliferation and reduces neurogenesis in hippocampus of mice with IFN-␣-induced depression-like behaviour [37]. Thus, it is possible that the increased quinolinic acid level arise form activated hippocampal microglia producing the neurotoxic compound that can affect neurogenesis.…”
Section: Ifn-˛-dependent Changes In the Tryptophan-kynurenine Pathwaymentioning
confidence: 99%
“…A dampened type I IFN response in the brain may be important for proper development of the newborn brain because multiple lines of evidence suggest that altering the cytokine balance in the brain can have profound developmental consequences (36,37). Specifically, intracranial inoculation of type I IFNs alone in mice has been shown to result in neurologic deficits later in life (38). Taken together, these results may suggest specific dampening of the IFN response in the newborn brain to avoid a cytokine response that could be detrimental to proper development.…”
Section: Discussionmentioning
confidence: 99%
“…Ці властивості обумовлюють застосування інтер-феронів під час розвитку інфекції, канцерогенезі [14]. Відомо, що ІФН діє на клітини ендотелію, спричиняючи антиангіогенний ефект [6; 9].…”
Section: вплив рекомбінантного інтерферону альфа на електричну активнunclassified
“…Інтерферони (ІФН) являють собою ро-дину цитокінів з плейотропною дією, що включає в себе інгібування вірусної реплікації, клітинної про-ліферації і активацію імунної системи. Рецептори до ІФНів експресуються на всіх клітинах організму.Ці властивості обумовлюють застосування інтер-феронів під час розвитку інфекції, канцерогенезі [14]. Відомо, що ІФН діє на клітини ендотелію, спричиняючи антиангіогенний ефект [6; 9].…”
unclassified